LEGAL REGULATION OF HEALTH CARE IN AVIATION SPHERE - Сопілко, І. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article examines the current state, system and prospects of legal regulation of health care in the aviation industry.